2011
DOI: 10.1007/s00894-011-1145-x
|View full text |Cite
|
Sign up to set email alerts
|

Homology modeling, molecular dynamics and QM/MM study of the regulatory protein PhoP from Corynebacterium pseudotuberculosis

Abstract: Corynebacterium pseudotuberculosis is a facultatively intracellular Gram-positive bacterium that causes caseous lymphadenitis, principally in sheep and goats, though sometimes in other species of animals, leading to considerable economic losses. This pathogen has a TCS known as PhoPR, which consists of a sensory histidine kinase protein (PhoR) and an intracellular response regulator protein (PhoP). This system is involved in the regulation of proteins present in various processes, including virulence. The regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Recently, we have used homology modeling, molecular docking and Molecular Dynamics (MD) simulations to study different biomolecular systems [45][47]. In this report, we propose a complete 3D model of HIV Vif by the ab initio approach.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have used homology modeling, molecular docking and Molecular Dynamics (MD) simulations to study different biomolecular systems [45][47]. In this report, we propose a complete 3D model of HIV Vif by the ab initio approach.…”
Section: Introductionmentioning
confidence: 99%
“…10. It has been reported that the aspartate receptor of the activation signal is View Article Online the Asp59 residue (phosphorylation is absolutely conserved) 26 that is located at the N-terminal receiver domain of the response regulator of the PhoP protein, which along with Asp15 has an important role in Mg +2 binding. It has already been established experimentally that this compound possesses antibacterial activity.…”
Section: Active Site Residues Identification and Docking Analysismentioning
confidence: 99%
“…Recently, we have used homology modelling to determine 3D structure of the regulatory response protein (PhoP) of Corynebacterium pseudotuberculosis [10], sialidases from Trypanosoma brucei and Trypanosoma evansi [11] and O-glycoprotein 2-acetamino-2-deoxy-β-D-glucopyranosidase [12]. Herein, we have used homology modelling [9] to describe the 3D structure of the enzymes involved in cytoplasmic steps of biosynthesis of peptidoglycan, namely GlmS, GlmM, GlmU, MurA, MurB, MurC, MurD, MurE and MurF.…”
Section: Introductionmentioning
confidence: 99%